Synthesis of a Series of New 6-nitrobenzofuran-2-carbohydrazide Derivatives with Cytotoxic and Antioxidant Activity - Taha, Muhammad; Sultan, Sadia; Mohamad, Azlan; Syed Adnan, Ali Shah; Jamil, Waqas; Swee, KeongYeap; Syahrul, Imran; Akhtar, Muhammad Nadeem; Seema, Zareen; Nor Hadiani, Ismail; Ali, Muhammad (Elsevier, 2017)
6-nitrobenzofuran-2-carbohydrazide Schiff base derivatives have been synthesized and their structure has been confirmed via H1NMR, Mass spectrometry and elemental (CHN/S) analysis. These synthesized analogs showed significant cytotoxic and antioxidant activity. Doxorubicin (IC50 = 0.94 ± 0.20 μM) and n-propyl gallate (IC50 = 30.30 ± 0.40 μM) were used as standard in cytotoxic and antioxidant activities, respectively. Compound 1 (IC50 = 3.30 ± 0.90 μM), 2 (IC50 = 2.70 ± 0.25 μM), 3 (IC50 = 2.70 ± 0.25 μM), 10 (IC50 = 2.70 ± 1.10 μM), 11 (IC50 = 1.00 ± 1.20 μM), and 17 (IC50 = 3.75 ± 0.90 μM) showed excellent while 21 (IC50 = 7.50 ± 0.60 μM) and 28 (IC50 = 7.50 ± 0.66 μM) showed moderate anti cancer activity. Furthermore, compound 10 (IC50 = 17.50 ± 0.85 μM), 11 (IC50 = 24.20 ± 0.55 μM), 12 (IC50 = 21.10 ± 1.58 μM), 13 (IC50 = 14.60 ± 0.32 μM), 14 (IC50 = 29.20 ± 0.75 μM) and 15 (IC50 = 9.26 ± 0.15 μM) showed better antioxidant activity than the standard n-propyl gallate. This study will be useful to develop potential lead molecules with cytotoxic and antioxidant potential.